HUBUNGAN ANTARA KEPATUHAN PENGGUNAAN APD DENGAN KEJADIAN KECELAKAAN KERJA KARYAWAN DI PT. STI TBK. CIKUPA KABUPATEN TANGERANG TAHUN 2018 - Rina Puspitasari; Desy Dwi Nurcahyati (Jurnal Kesehatan, 2018)
Every worker or company no one wants the accidentis a natural instinctand universal for every living creature in the world. Work accident is an occurrence of accident srelated to th eactivity or activities in the work. This study aimed to determine the factors associated with the incidence of employee accidents in the company. This research uses descriptive correlation research designand crosssectional approach. Using quantitative research design with analytical surveymethod and crosssectional approach. The results of this study showed that respondents who had moderateworkaccident as many as 12 workers (15%) andthosewho had light work accidents were 68 workers (85%) Statisticaltestresultsusing Chi Square Test theresult of statistictestthereis a significant correlation between employee compliance with workaccident (p value = 0,013). Suggestions of thisresearchareexpectedtoincreaseawareness of respondentsinmaintainingoccupationalsafetyandhealth (K3) and improve complian ceintheuse of PPE (Personal Protective Equipment) and obeyallrules that have been set in the company to avoid work accidents.